NECESSARY ADEQUACIES IN ADAPTED BASKETBALL ACTIVITIES (Fiep Bulletin - online, 2015)
The aim of this qualitative study was to identify the necessary adequacies in two adapted basketball sections that were composed by 10 activities each and lasted 98 and108 minutes respectively. The individuals who took part in this sample were: I1: 19 years-old  Down ´s Syndrome (DS), I2: 29 years-old  brain paralysis with athetosic quadriparesy, I3: 20 years-old - mentally handicapped with behavior disorder, I4: 17 years-old  Asperger's Syndrome and I5: 20 years-old  DS. Films and written registers were used in collecting and analyzing data. Results: I1 needed stimuli and only took part in some activities when he was directed and received additional information and orientation due to his slowness and difficulty in understanding. I2 needed adequacies due to motor difficulties, being the most frequent ones: help to dislocate, to reach materials and adequacy of movements. I3 needed only some information, as which kind of pass he should perform, demonstrations on how to turn, among other things, performing autonomously most of the time. I4 performed almost all the tasks without difficulty an on his own, needing just incentive to throw in the arches and demonstrations on how to perform the turn around himself. I5 needed stimuli to throw, to perform the zig-zag and demonstrations on how to perform the turn. The necessary adequacies were related to: additional information and demonstrations, stimuli and incentive, more time to accomplish the tasks and necessity to modify movements due to motor difficulties. Regarding the material adequacy, it was noticed that the use of different sizes of balloons and balls made it easier the execution of the educationals and made it possible to increase gradually the task complexity.
Keywords: Adequacies; handicapped individuals; basketball